Dragon kingdom of Wrenly. Book 3, Night hunt - Quinn, Jordan (Quinn, Jordan. Dragon Kingdom of Wrenly, 2021)
"Ruskin is back on Crestwood to witness the Night Hunt, a legendary event wherein the bravest young dragons on Crestwood are chosen to participate in a high-stakes scavenger hunt"--